A prospective study to assess the efficacy of 4% articaine, 0.5% bupivacaine and 2% lignocaine using a single buccal supraperiosteal injection for maxillary tooth extraction - Deepak Chandrasekaran; Ravindran Chinnaswami; K Shanthi; A Emmanuel Dhiravia Sargunam; K Santhosh Kumar; Tharini Satheesh (Journal of Pharmacy and Bioallied Sciences, 2021)
Introduction: The aim of this study was to demonstrate if articaine hydrochloride administered alone as a single buccal infiltration in maxillary tooth extraction can provide adequate palatal anesthesia as compared to buccal and palatal injection using lidocaine and bupivacaine. Materials and Methods: A prospective double-blinded trial was conducted on 150 patients who required maxillary tooth extraction. The patients were divided into three different groups consisting of 50 patients each. Each group was administered with 4% articaine into buccal vestibular mucosa of the tooth to be extracted, 2% lignocaine and 0.5% bupivacaine was injected into buccal and palatal side of the tooth to be extracted, respectively. Following the tooth extraction, all patients were asked to complete a 10-score Visual Analog Scale (VAS) and 5-score facial pain scale (FPS) to assess the pain on extraction. Results: According to the VAS and FPS scores, the pain on extraction between buccal infiltration of articaine and the routine buccal and palatal infiltration of lignocaine was statistically significant. Conclusion: The routine use of a palatal injection for extraction of maxillary teeth may not be required when articaine is used as a local anesthetic solution.